2015
DOI: 10.1007/s40565-015-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-time impact of power balancing on power system operation with large scale integration of wind power

Abstract: Highly wind power integrated power system requires continuous active power regulation to tackle the power imbalances resulting from the wind power forecast errors. The active power balance is maintained in real-time with the automatic generation control and also from the control room, where regulating power bids are activated manually. In this article, an algorithm is developed to simulate the activation of regulating power bids, as performed in the control room, during power imbalance between generation and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In current power system operations, conventional power plants are responsible for providing system services, while renewable generation sources (WPPs) are exempted for providing the required support [1,3,24,25]. Studies have shown that WPPs can also contribute actively to power balancing control [4,5,26].…”
Section: System Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In current power system operations, conventional power plants are responsible for providing system services, while renewable generation sources (WPPs) are exempted for providing the required support [1,3,24,25]. Studies have shown that WPPs can also contribute actively to power balancing control [4,5,26].…”
Section: System Modelingmentioning
confidence: 99%
“…Large-scale integration of renewables affects the active power balance control in the real-time operation of the power system [1,2]. Traditionally, conventional power plants are responsible for providing system services to maintain secure operation of the power system [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the dispatching systems of power grid are facing more and more uncertainties related to wind power forecasting errors, the scheduling system of power grid has insufficient information to handle these uncertainties under the fast increasing scale of wind power integration/interconnection among various energies. Therefore, the current method demanding accurate information cannot fulfill the need in the real work of the scheduling system [20][21][22][23]. It is impossible to take the forecasting value of wind power as the effective power output in day-ahead dispatching plan based on the reliability of power supply during the peak load period.…”
Section: Introductionmentioning
confidence: 99%
“…The safe operation of the power system is based on a reliable power supply and accurate load forecasting. However, substantial indeterminacy caused by large-scale wind power integration presents the power system with significant challenges [1][2][3][4]. As the scale of wind power integration continues to increase, fossil energy power generation is gradually subjected to certain constraints.…”
Section: Introductionmentioning
confidence: 99%